#### Answer

\[\left( f\circ g \right)\left( 0 \right)=-7\]

#### Work Step by Step

Since the value of the given composite function can be obtained using the definition of composite functions and the values of $f$ and $g$ at the required points, t can be obtained very easily from the above equations.
Now, $g\left( 0 \right)=4\left( 0 \right)-1=-1$ , thus we have
$\begin{align}
& \left( f\circ g \right)\left( 0 \right)=f\left( g\left( 0 \right) \right) \\
& =f\left( -1 \right) \\
& =2\left( -1 \right)-5 \\
& =-7
\end{align}$